2020
DOI: 10.1177/1756284820965790
|View full text |Cite
|
Sign up to set email alerts
|

Rapid test detection of anti-infliximab antibodies: performance comparison with three different immunoassays

Abstract: Background and Aims: Therapeutic drug monitoring (TDM) of infliximab (IFX) and anti-infliximab antibodies (ATIs) is essential for treatment optimisation in inflammatory bowel disease (IBD) patients. The aim of this study was to estimate and compare the agreement and accuracy between a new rapid test and three established enzyme-linked immunosorbent assays (ELISAs) to quantify ATIs levels, and to evaluate the impact of exogenous IFX on the performance of these assays. Methods: We analysed 200 serum samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Third, patients with antidrug antibodies were excluded and their presence was not assessed during the study, although such an interaction with rapid tests has been previously reported. 36 Finally, for pragmatic reasons, the study did not examine the best way of implementing proactive drug level monitoring with at-infusion measurement of infliximab levels and did not explore changing infusion intervals but provided data on which such a question could be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Third, patients with antidrug antibodies were excluded and their presence was not assessed during the study, although such an interaction with rapid tests has been previously reported. 36 Finally, for pragmatic reasons, the study did not examine the best way of implementing proactive drug level monitoring with at-infusion measurement of infliximab levels and did not explore changing infusion intervals but provided data on which such a question could be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…32,145 However, as the number of such tests increases, their quality needs to be assessed and their accuracy compared with the commonly used laboratory measurements of drug concentrations and ADA to check for potential discrepancies. [146][147][148]…”
Section: Point-of-care Assaysmentioning
confidence: 99%
“…Serum CRP concentrations were determined using a highly sensitive assay (Konelab™, Thermo Scientific, Finland). FC and IFX levels were measured using the Quantum Blue ® fCAL and IFX quantitative assays, respectively (Bühlmann Laboratories, Switzerland), while anti‐IFX antibody levels were quantified with a validated in‐house ELISA (anti‐human lambda chain assay, 1.2–100 μg/mL; values below 1.7 μg/mL were considered negative) 10,11 . All determinations were performed in a central laboratory.…”
Section: Methodsmentioning
confidence: 99%